Johannesburg inner city’s appropriated buildings: resident’s responses to vulnerability and precarious living conditions - Ngwenya, Makale (My University, 2017)
Johannesburg like many rapidly urbanising cities around the world has the problem of a lack of affordable accommodation and inadequate access to basic services (Tissington, 2013). Residents in the inner city use spaces and buildings in a way that reclaims the promises of the city to a better life. As historian and cultural theorist Abdou Maliq Simone (2004) has noted people within African Cities have a probable tendency to improvise. In this research I use the concept of evolutionary resilience, which has been described to account for individuals and households ability adapt in constantly changing environments (Simmie & Martin, 2010) to explore the responses of residents to precarious living conditions and vulnerability that is created by conditions of insecure tenure and evictions. There is little comparative empirical research about how inner city residents talk about their lives and experiences. This research contributes to filling this gap by examining the experiences of residents and highlighting the ways in which as Cirugeda (2004) points to, residents often use empowerment strategies that encourage inhabitants to subvert laws and regulations, in order to maximise self-help by appropriating structures for better living conditions (Cirugeda 2004). This research utilises in depth interviews that were conducted within selected buildings in the inner city using a semi structured interview guide. The objective is to examine the strategies of coping with the exposure to risk and how individuals respond to these shocks. Şoitu (undated) states that vulnerability is a situation of social, economic and physiological need when individuals are marginalised and resilience is a personal resource that allows individuals to face stress and shocks and provides strength (Şoitu, undated). This research finds that there are many difficulties, threats and vulnerabilities that residents are exposed to and residents invoke various strategies and responses for coping. KEYWORDS ‘Bad buildings’, inner city, Johannesburg, vulnerability, evolutionary resilience, precarious living conditions, basic services, insecure tenure
Thesis is submitted in partial fulfilment for the degree of Master of the Built Environment (Housing), to the Faculty of Engineering and the Built Environment, School of Architecture and Planning at the University of the Witwatersrand, Johannesburg, 2017
Keywords: Inner cities--South Africa--Johannesburg; Apartments--South Africa--Johannesburg; Rental housing--South Africa--Johannesburg; Apartment dwellers--South Africa--Johannesburg